Prints from German Publishing Houses in the Dominican Monks’ Book Collection in Różanystok (Poland). Contribution to the Books’ Circulation in Europe from the 17th to the 19th Century - Katarzyna Zimnoch (Archiwa, Biblioteki i Muzea Kościelne)
The aim of the paper is to present a fragment of the 17th–19th century book circulation in Europe with special emphasis put on the flow of the prints from German publishing houses into Poland. The objective of the analysis is the book collection owned by the Dominican Order based in Różanystok in the borderland between The Crown of the Kingdom of Poland (The Crown) and the Grand Duchy of Lithuania. The source for the study comprised handwritten inventories in the Dominican monastery library dated 1828 and 1846. The book collection was analysed for the geography of publishing and chronology, and compared to other Dominican libraries (in Borek Stary, Kalwaria Żmudzka, Lviv, Poporcie, Wrocław). The analysis resulted in confirming the existence of 75 German prints (12.88% of the studied book collection) originating from German printing houses in: Augsburg, Dillingen, Frankfurt am Main, Cologne, Leipzig, Mainz, Nuremberg, Paderborn and Sulzbach. The proposed studies point to the specific examples of libraries in Central and Eastern Europe reached by the prints from German publishing houses and indicate the channels for the transfer of cultural and religious contents from specified publishing centres over the said period.